Impact of Motorway Al on Development of Tourism in the Sibenik-Knin County - Protega, Veselko; Božić, Nikica; Lučić, Zlatko (Promet - Traffic&Transportation, 2007)
The work studies the impact of the changed traffic flows(moto1way Al) on the development of the tourist economy ofthe Sibenik-Knin County. The selected three-year period (2003- 2005) includes three phases of different construction levels ofthe motorwayAl Zagreb- Split in the area of the Sibenik-KninCounty. This raises the issue of the cause-effect relation ofbetter traffic connections and the improvement of tourism aswell as the compatibility of the new road network with the tendenciesof reconstructing the tourist offer with special referenceto unbalanced development of different destinations.